Complete Genome Sequence of Mesorhizobium ciceri Strain R30, a Rhizobium Used as a Commercial Inoculant for Chickpea in Argentina - Foresto, Emiliano; Revale, Santiago; Primo, Emiliano David; Nievas, Fiorela Lujan; Carezzano, Maria Evangelina; Puente, Mariana Laura; Alzari, Pedro; Martínez, Mariano; Ben-Assaya, Mathilde; Mornico, Damien; Santoro, Valeria Maricel; Martínez-Abarca, Francisco; et al. (American Society for Microbiology, 2024)
We report the complete genome sequence of Mesorhizobium ciceri strain R30, a rhizobium strain recommended and used as a commercial inoculant for chickpea in Argentina. The genome consists of almost 7 Mb, distributed into two circular replicons: a chromosome of 6.49 Mb and a plasmid of 0.46 Mb.